2003
DOI: 10.1007/s00441-003-0740-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metabotropic glutamate receptor group I in rat gustatory papillae

Abstract: Taste-metabotropic glutamate receptor 4 (taste-mGluR4) and the heteromers of T1R1 and T1R3 are candidate receptors involved in the sense of umami (monosodium glutamate) taste. Although the expression of group III mGluRs (taste-mGluR4) has been demonstrated in taste tissues, no mention has been made of the expression of group I mGluRs (mGluR1 and mGluR5) in taste tissues. We examined the expression of mGluR1 and mGluR5 in rat gustatory tissues by using reverse transcription-polymerase chain reaction (RT-PCR), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 42 publications
0
68
0
Order By: Relevance
“…Brain-expressed mGluR1 and mGluR4 are shown to be expressed in rat taste cells in the posterior tongue. 36,37) Taken together, all these results indicate involvement of mGluR1 and mGluR4 in addition to T1R1/T1R3 in umami detection.…”
Section: Effects Of Antagonists For Mglurs On Umami Responsesmentioning
confidence: 62%
“…Brain-expressed mGluR1 and mGluR4 are shown to be expressed in rat taste cells in the posterior tongue. 36,37) Taken together, all these results indicate involvement of mGluR1 and mGluR4 in addition to T1R1/T1R3 in umami detection.…”
Section: Effects Of Antagonists For Mglurs On Umami Responsesmentioning
confidence: 62%
“…9) Now, several types of GLU receptors are found to exist at the apical membrane of the taste cells (type II taste cells) including the T1R1/T1R3, metabotropic GLU receptor type 1 and 4 (mGluR1 and mGluR4), taste mGluR1, and taste mGluR4. [10][11][12][13][14] Activation of receptors produces changes in intracellular second messenger levels and open/close state of membrane channels to cause excitation of taste cells. The activation of taste cells is transmitted to the taste nerves through the release of a transmitter ATP.…”
Section: Taste Mechanismsmentioning
confidence: 99%
“…We investigated changes in palatability, taste quality, and taste intensity of umami substances using a 48-h 2-bottle preference test, a CTA test, and gustatory nerve Previous studies have identified three putative G protein-coupled receptors for umami substances: tastemGluR1, 14) taste-mGluR4, 15,16) and the amino-acid receptor T1R1 镁 T1R3 heterodimer. 17,18) Synergy, a hallmark of umami taste, was observed not only at the individual level but also at the cellular level.…”
Section: Discussionmentioning
confidence: 99%